IoT based monitoring system of power supplies using solar panel and PLN - Al Amin, Athah; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The advancement of Internet of Things (IoT) technology has opened new opportunities in energy management, especially for power supply monitoring systems that combine solar panels and the PLN grid. This study designs and implements an IoT-based monitoring system to observe voltage levels of 5VDC, 12VDC, and 24VDC in real-time using INA219 sensors, a 20A PWM Solar Charge Controller, a 12V 5Ah battery, and a NodeMCU ESP32 connected to the Blynk application. The system features automatic switching from solar to PLN when abnormal conditions such as overcurrent (>100mA) or voltage drops occur. Testing under normal and fault conditions shows that the system effectively maintains stability, switches power sources automatically, and provides real-time notifications, demonstrating its efficiency and suitability as a reliable, environmentally friendly energy management solution